2014
DOI: 10.1080/10618562.2014.922179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of linear, inviscid, viscous, and reduced-order modelling aeroelastic solutions of the AGARD 445.6 wing using root locus analysis

Abstract: Reduced-order modelling (ROM) methods are applied to the Computational Fluid Dynamics (CFD)-based aeroelastic analysis of the AGARD 445.6 wing in order to gain insight regarding well-known discrepancies between the aeroelastic analyses and the experimental results. The results presented include aeroelastic solutions using the inviscid Computational Aeroelasticity Programme-Transonic Small Disturbance (CAP-TSD) code and the FUN3D code (Euler and Navier-Stokes). Full CFD aeroelastic solutions and ROM aeroelastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In contrast, the results for three considered modes show a different behavior, since the values for both the FSI and the FR are much smaller than the experimental values and the respective quantities at N 2. This is due to the fact that the third mode becomes unstable, as was already noted by Silva et al [40]. Therefore, it is confirmed that the inviscid AER-Eu solver also leads to this instability for the AGARD 445.6 wing at supersonic conditions.…”
Section: E Numerical Flutter Analysissupporting
confidence: 82%
See 4 more Smart Citations
“…In contrast, the results for three considered modes show a different behavior, since the values for both the FSI and the FR are much smaller than the experimental values and the respective quantities at N 2. This is due to the fact that the third mode becomes unstable, as was already noted by Silva et al [40]. Therefore, it is confirmed that the inviscid AER-Eu solver also leads to this instability for the AGARD 445.6 wing at supersonic conditions.…”
Section: E Numerical Flutter Analysissupporting
confidence: 82%
“…If the inflow becomes supersonic, the flutter speed index and the frequency ratio are increased substantially for N 2, while the overprediction of those indicators in terms of the experimental results was already noted by Lee-Rausch and Batina [39], as well as numerous other publications for Euler-equations-based flutter computations (see also [40]). In contrast, the results for three considered modes show a different behavior, since the values for both the FSI and the FR are much smaller than the experimental values and the respective quantities at N 2.…”
Section: E Numerical Flutter Analysismentioning
confidence: 60%
See 3 more Smart Citations